Genetic parameters and genotype × environment interaction in Pinus taeda clonal tests - Braga, Rayssa Chaves; Paludeto, João Gabriel Zanon; Souza, Bruno Marchetti; Aguiar, Ananda V.; Pollnow, Maria Fernanda M.; Carvalho, Ana Gabriela Monnerat; Tambarussi, Evandro Vagner (Forest ecology and management, 2020)
•Clonal tests for Pinus taeda commercial wood production show promising results.•Genotype × environment interactions have limited impact on growth.•Tested clones include genotypes adapted to different environments.•Two breeding zones are suggested to improve Pinus taeda breeding programs. Pinus taeda (loblolly pine) is a widely-cultivated conifer that is particularly prevalent in the southeast United States and Southern Brazil. Some companies in Brazil are working with the third generation of improvement and other clonal tests of this species. The present study analyzed the interaction of genotype × environment (G × E) in clonal tests of loblolly pine planted in the South and Southeast regions of Brazil. For this, 75 clones and three commercial controls were tested using a randomized block design, with eight replications, and one plant per plot repeated across four sites. Measurements were performed at 11 years of age for diameter at breast height (dbh), total height, and volume. The GGE biplot and the Harmonic Mean of the Relative Performance of Genotypic Values (MHPRVG) methods were used to study the effects of G × E on dbh. The dbh was chosen because it is less subject to measurement errors and highly correlated with volume. The mean of heritability in the broad-sense among sites for dbh was high (0.89), as was the genotypic correlation between sites (0.78). Among the four tested environments, two sites can be considered as one mega-environment. Through the analysis, it was possible to verify the low magnitude of the effects of G × E on the tested clones. The best performing clones among all tests can be selected to produce commercial stands in areas with similar environmental characteristics to the sites tested herein. Thus, the composition of two breeding zones is recommended considering the tested clones.